Preliminary Phytochemical Screenings and Pharmacological Activities of Three Medicinal Plants of Bangladesh - Ibrahim, Mohammed; Kuddus, Md Ruhul; Hossain, Md Aslam; Mansur, Muhammad Abdullah Al; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The present study was designed to evaluate the preliminary phytochemical screening and antimicrobial, antidiarrheal, anti-inflammatory, analgesic, antipyretic, anxiolytic, thrombolytic and membrane stabilizing properties of the methanolic extract of three medicinal plants Perilla ocymoides L., Murraya koenigii (Linn.) Spreng., Baliospermum montanum (Wild.) Muell growing in Bangladesh. In antimicrobial test, maximum zone of inhibition was found against Salmonella typhi (18.0 mm) and Escherichia coli (17.0 mm) by B. montanum extract. In the castor oil-induced antidiarrheal assay, the methanol extract of M. koenigii showed maximum 50% inhibition of defecation. During in-vitro anti-inflammatory test, the methanol extract of B. montanum at 500 μg/ml, b.w. revealed 39.62% inhibition of protein denaturation. Due to analgesia, the M. koenigii extract showed 53.29% inhibition of acetic acidinduced writhing reflex in experimental mice. Antipyretic effect of P. ocymoides, M. Koenigii and B. montanum extractives was assessed by Brewer’s yeast-induced pyrexia in mice. The B. montanum extract possesses significant anxiolytic effect that was evidenced by both hole cross test and open field test in mice. In thrombolytic assay, the highest activity (57.81%) was observed by B. montanum extract. Results of the preliminary phytochemical screenings demonstrated the presence of alkaloids, glycosides, flavonoids, reducing sugars, gums etc. Dhaka Univ. J. Pharm. Sci. 16(2): 195-203, 2017 (December)